W poszukiwaniu rozumowania matematycznego najmłodszych uczniów – doniesienie z badań wdrożeniowych - Alina Kalinowska-Iżykowska (Problemy Wczesnej Edukacji)
Mathematical reasoning is a crucial competence for the construction of useful knowledge. The text presents selected results of the study of students of the third grade of an elementary school in the field of text task solving. The conducted educational experiment showed the potential of solving non-standard tasks for developing the reasoning of mathematically weaker students. Contact with tasks that require independent mathematizing allowed to reduce the number of students with the lowest results in the post test. The ways of understanding the role of drawing in exploring mathematical relations described in the task were analysed.